Synthesis And Antimicrobial Activity Of N-Phthilimido And Acetimido Derivatives From Amino Acids And Hthalicanhydrides - C.UMA MAHESWARA REDDY; B.JAYAKAR; R. SRINIVASAN (International Journal of Pharma and Bio Sciences, 2010)
The phthaloyl and acetyl group are common protecting groups from are common protecting group for amines in organic synthesis1 and are also important pharmacophores2. Common method are imide synthesis include dehydrative condensation of an anhydride and amino acid at high temperature, the acid-catalyzed cyclization of N-substituted amic acid. Abdol Reza Hajipour3, rapidly synthesised Phthalimide derivatives by microwave irradiation. A simple extremely fast, and high yielding method for the reaction of phthalic anhydride with a number of amino acids using microwave irradiation under solventless dry condition has been developed. The aim of the study was to design, synthesize and investigate the antimicrobial and antifungal activities, anticancer activities of some α N-Phthilimido and acetylated derivatives of amino acids. The chemical structures of the titled compound were confirmed by IR, 13CNMR and elemental analysis. All the compounds were screened for antimicrobial activity against gram positive, gram negative bacteria (Escherichia coli, Klebsiella, Staphylococcus epidermitis, Bacillus cereus, Micrococcus leteus, Staphylococcus aureus) and fungal strains (Candida albicans, Aspergillus niger)